2020
DOI: 10.4018/ijcrmm.2020040102
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Perceived Value in Internet Shopping

Abstract: In recent years, the trend of online retailing has become one of the most imperative uses of technology with the development and ease of accessibility of the internet. The activity of online shopping is considered to be one of the significant aspects of online retailing and has been emerging as an essential part of consumers' lifestyle. Besides various advantages, consumers feel different types of perceived risks involved in online shopping. Therefore, it is crucial to identify the factors affecting consumers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…Conferring to Soares et al (2022), perceived usefulness has a positive relationship with online purchase intent, and perceived ease of investment has a significant positive association with perceived usefulness and online purchase intent. It is essential to recognise the buyers through their likenesses and divide them based on the dimensions that are exploding while making an online buying decision (Katta & Patro, 2020). It is the satisfaction derived from a comparison of consumer expectations and experience (Khristianto et al, 2012).…”
Section: Purchase Decisionmentioning
confidence: 99%
“…Conferring to Soares et al (2022), perceived usefulness has a positive relationship with online purchase intent, and perceived ease of investment has a significant positive association with perceived usefulness and online purchase intent. It is essential to recognise the buyers through their likenesses and divide them based on the dimensions that are exploding while making an online buying decision (Katta & Patro, 2020). It is the satisfaction derived from a comparison of consumer expectations and experience (Khristianto et al, 2012).…”
Section: Purchase Decisionmentioning
confidence: 99%
“…A conveniência representa a possibilidade de acesso a um aplicativo de celular a qualquer hora e em qualquer lugar (Liu et al, 2017). A usabilidade, por sua vez, consiste na percepção de qualidade e facilidade de uso do app (Katta & Patro, 2020). A confiabilidade remete a um fator essencial para tomada de decisão em compras on-line e para lealdade ao aplicativo (Yuen et al, 2019;Cho et al, 2019).…”
Section: Aplicativos De Delivery De Comida E Percepção De Valorunclassified
“…Consumer perception represented its buyer evaluation of the functionality of goods centered on the understanding of what was gained and delivered (Pham, Tran, Misra, Maskeliunas & Damasevicius, 2018). The customer's perceived value is described as an overall measure of a trade-off between the apparent performance of the goods or service obtained and the overall development or service acquisition expense (Katta & Patro, 2020). Argue that meaning perceived is a term that blends the shopping value with the commodity value (Fang, Wen, George & Prybutok, 2016).…”
Section: Perceived Valuementioning
confidence: 99%
“…Besides, the interpretation of the value of customers would affect their propensity to revisit a product or service provider (Katta & Patro, 2020). Study studies also showed that perceived worth could be better than happiness or efficiency than an indicator of repurchase intention (Pham et al, 2018).…”
Section: Perceived Valuementioning
confidence: 99%
See 1 more Smart Citation